2019
DOI: 10.1016/j.jclepro.2019.02.207
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural demand response for decarbonizing the electricity grid

Abstract: 1Historically, the focus of the agricultural industry has been increasing profit through maximizing crop yield. Costs for energy and water are small compared to equipment and personnel, and are thus often overlooked. However, energy costs for irrigation are increasing and could be exacerbated with declining water levels in many Western states. This trend has motivated many farmers to explore sustainable irrigation water and energy management practices. Much of this new focus has been directed towards the adopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…18 In 2019, a prominent research study suggested the deregulation in the agricultural industry to facilitate the integration of renewable energies to electricity markets. 19 The study stated that farmers not only can provide a great deal of flexibility to the grid but also can monetize their energy generation. The study suggested the irrigation systems as potential demands to overcome the intermittency of renewable energies.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…18 In 2019, a prominent research study suggested the deregulation in the agricultural industry to facilitate the integration of renewable energies to electricity markets. 19 The study stated that farmers not only can provide a great deal of flexibility to the grid but also can monetize their energy generation. The study suggested the irrigation systems as potential demands to overcome the intermittency of renewable energies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Inequality (17) limits the power generation of DGs to lower and upper thresholds. Finally, the constraints (18) and (19) show the ramp-up and ramp-down rates of the DG units, respectively.…”
Section: Thermal Generation Unitsmentioning
confidence: 99%
“…However, this is not complete as some TCLs may be forced to switch due to the temperature constraint (1). The upper bound should then be increased by d on k −1 and decreased by d off k−1 .…”
Section: Power Deviation Limitsmentioning
confidence: 99%
“…The first is, s τ : which counts the total number of TCL switches normalized by the number of TCLs. The desired value of s τ is small, as a smaller number of total switches is preferred, but some amount of switching is required for providing VES and maintaining thermal comfort (1). The second metric is,…”
Section: Parametric Studymentioning
confidence: 99%
See 1 more Smart Citation